Impact of horizontal and vertical posterior pole steepness on the dimensions of idiopathic macular hole - Niroj Kumar Sahoo; Jay Chhablani; Ashika Patil; Ninan Jacob; Mudit Tyagi; Srinivas Rao Podili; Rahman Khan Pathan (International Journal of Retina and Vitreous, 2025)
Abstract Background Macular holes (MH) vary immensely with respect to size and shape among different individuals. In an attempt to see if the curvature of the retinal pigment epithelium has any role, we aimed to analyse the influence of horizontal and vertical posterior pole steepness on idiopathic macular hole dimensions. Methods This was a retrospective observational study done in eyes with a diagnosis of idiopathic macular hole. Various MH parameters like baseline hole parameters like minimum linear diameter (MLD), baseline hole diameter (BHD), and hole angles were calculated. Steepness in the form of tangent angles was measured in both horizontal and vertical meridian at 6 mm and under the MH margins at 1.5 mm. Results 52 eyes of 52 patients were included. Horizontal MLD showed weak correlation with average horizontal hole angle (r=-0.28, p = 0.04); average vertical hole angle (r=-0.28, p = 0.04). Horizontal BHD showed significant correlation with the horizontal hole margin tangent apical angle (r=-0.46, p = 0.001); average horizontal hole angle (r=-0.45, p = 0.001). Vertical MLD showed correlation with average horizontal hole angle (r=-0.28, p = 0.04) and average vertical hole angle (r=-0.33, p = 0.03). Vertical BHD showed correlation with horizontal hole margin tangent apical angle (r=-0.38, p = 0.004) and vertical hole margin tangent apical angle (r=-0.31, p = 0.03); vertical 6 mm tangent apical angle (r=-0.36, p = 0.01). On multivariate regression analysis, factors favouring a type 2 closure include, lower superior hole angle and higher inferior to superior tangent base angle ratio. Conclusion Hole margin tangent angles were seen to correlate with the size and shape of the hole. Future studies with bigger sample size are required to validate it further.